The Effect of Pagoda Leaves Extracts on the Level of IL-6 of Female Rats Induced by Staphylococcus aureus - Ibrahim, Fitriana; Prihantono, Prihantono; Ahmad, Mardiana; Siagian, Nurul Aini (Health Notions, 2018)
The extract of Pagoda leaves can play roles as an anti-inflammatory, antioxidant, and antibacteria. Interleukin 6 (IL-6 henceforth) is the primary mediator in responding to the inflammation, while mastitis is caused by bacteria often found in the increased level of IL-6. This research aimed to unveil the effect of giving the extracts of Pagoda leaves on the level of IL-6 of female rats (Sprague dawley therefore) induced by staphylococcus aureus bacteria. This true experimental research employing pre- and post-test control design used eighteen rats chosen randomly. All rats were divided into three groups, namely negative control (placebo), positive control (amoxicillin 9.6 mg/ml/kgBB/hari/oral) and treatment group (amoxicillin 9.6 mg/ml/KgBB + EDP 50 mg/ml/KgBB/hari/oral). All groups were induced by S.aureus 0.2x108 CFU. Treatment was given for five days. Investigating the level of IL-6 was done using ELISA method. The data were anaylized using ANOVA formula followed by post hoc. The empirical findings showed that there was a difference in terms of the level of IL-6 in all of the groups Â±24 before and after the induction of S.aureus. The result of investigating the level of IL-6 in the post-test was significant (Ï = 0.00), meaning that there was a significant difference, in which the negative control group, the level of IL-6 was insacalating; while it was dipping in both the positive and treatment groups. However, the treatment group experienced the most significant drop in terms of the level of IL-6. It can be concluded that Pagoda leaves can be used as a complementary therapy for mastitis illness caused by the S.aureus bacteria.